Alkali Metal Variation and Twisting of the FeNNFe Core in Bridging Diiron Dinitrogen Complexes - McWilliams, Sean F. (Inorg Chem, 2016)
[Image: see text] Alkali metal cations can interact with Fe–N(2) complexes, potentially enhancing back-bonding or influencing the geometry of the iron atom. These influences are relevant to large-scale N(2) reduction by iron, such as in the FeMoco of nitrogenase and the alkali-promoted Haber–Bosch process. However, to our knowledge there have been no systematic studies of a large range of alkali metals regarding their influence on transition metal–dinitrogen complexes. In this work, we varied the alkali metal in [alkali cation](2)[LFeNNFeL] complexes (L = bulky β-diketiminate ligand) through the size range from Na(+) to K(+), Rb(+), and Cs(+). The FeNNFe cores have similar Fe–N and N–N distances and N–N stretching frequencies despite the drastic change in alkali metal cation size. The two diketiminates twist relative to one another, with larger dihedral angles accommodating the larger cations. In order to explain why the twisting has so little influence on the core, we performed density functional theory calculations on a simplified LFeNNFeL model, which show that the two metals surprisingly do not compete for back-bonding to the same π* orbital of N(2), even when the ligand planes are parallel. This diiron system can tolerate distortion of the ligand planes through compensating orbital energy changes, and thus, a range of ligand orientations can give very similar energies.